Administration of anti-HIV-1 broadly neutralizing monoclonal antibodies with increased affinity to Fcγ receptors during acute SHIVAD8-EO infection - Dias, Joana; Fabozzi, Giulia; Fourati, Slim; Chen, Xuejun; Liu, Cuiping; Ambrozak, David R.; Ransier, Amy; Laboune, Farida; Hu, Jianfei; Shi, Wei; March, Kylie; Maximova, Anna A.; et al. (Nature communications, 2024)
Anti-HIV-1 broadly neutralizing antibodies (bNAbs) have the dual potential of mediating virus neutralization and antiviral effector functions through their Fab and Fc domains, respectively. So far, bNAbs with enhanced Fc effector functions in vitro have only been tested in NHPs during chronic simian-HIV (SHIV) infection. Here, we investigate the effects of administering in acute SHIV AD8-EO infection either wild-type (WT) bNAbs or bNAbs carrying the S239D/I332E/A330L (DEL) mutation, which increases binding to FcγRs. Emergence of virus in plasma and lymph nodes (LNs) was delayed by bNAb treatment and occurred earlier in monkeys given DEL bNAbs than in those given WT bNAbs, consistent with faster clearance of DEL bNAbs from plasma. DEL bNAb-treated monkeys had higher levels of circulating virus-specific IFNγ single-producing CD8 + CD69 + T cells than the other groups. In LNs, WT bNAbs were evenly distributed between follicular and extrafollicular areas, but DEL bNAbs predominated in the latter. At week 8 post-challenge, LN monocytes and NK cells from DEL bNAb-treated monkeys upregulated proinflammatory signaling pathways and LN T cells downregulated TNF signaling via NF-κB. Overall, bNAbs with increased affinity to FcγRs shape innate and adaptive cellular immunity, which may be important to consider in future strategies of passive bNAb therapy. In this work, the authors study the immunological and virological effects of administering either wild-type anti-HIV-1 broadly neutralizing antibodies (bNAbs) or bNAbs with a mutation that increases binding to Fc-gamma receptors (FcγRs) to rhesus macaques in the acute phase of SHIV AD8-EO infection.